A systematic review of methamphetamine precursor regulations - McKetin, Rebecca; Sutherland, R.; Bright, D.; Norberg, M. (Wiley-Blackwell Publishing Ltd., 2011)
Aims: To assess the effectiveness of methamphetamine precursor regulations in reducing illicit methamphetamine supply and use. Methods: A systematic review of 12 databases was used to identify studies that had evaluated the impact of methamphetamine precursor regulations on methamphetamine supply and/or use. The guidelines of the Effective Practice and Organization of Care Group (EPOC) of The Cochrane Collaboration were used to determine which study designs were included and assess their quality. Results: Ten studies met the inclusion criteria. These studies evaluated 15 interventions (13 regulations and two related interdiction efforts), all of which were located in North America. Interventions had consistent impacts across various indicators of methamphetamine supply and use. Seven of the 15 interventions produced reductions in methamphetamine indicators (ranging from 12% to 77%). Two of the largest impacts were seen following interdiction efforts, involving the closure of rogue pharmaceutical companies. There was no evidence of a shift into other types of drug use, or injecting use, although the impact on the synthetic drug market was not examined. Null effects were related largely to the existence of alternative sources of precursor chemicals or the availability of imported methamphetamine. Conclusions: Methamphetamine precursor regulations can reduce indicators of methamphetamine supply and use. Further research is needed to determine whether regulations can be effective outside North America, particularly in developing countries, and what impact they have on the broader synthetic drug market. Improved data on precursor diversion are needed to facilitate the evaluation of precursor regulations.